Spatiotemporally Continuous Marine Heatwaves: A Novel Clustering Approach Reveals Increasing Frequency, Duration, Area, Intensity, and Movement Distance - Jie Ren; Chunzai Wang; Yulong Yao (Geophysical Research Letters)
Abstract Marine heatwaves (MHWs) are extended periods of unusually warm ocean temperatures that significantly impact marine ecosystems. While most studies concentrate on temporal changes at a single point or spatial changes over a fixed duration, the combined daily progression of these changes in both space and time is still largely unexplored. Here, we employ observational data from a three‐dimensional perspective (latitude × longitude × time) to examine multidimensional characteristics of Spatiotemporally Continuous MHWs (SCMHWs) worldwide from 1982 to 2022. We categorize them into eight types based on duration, area, and mean intensity. Results of the three‐dimensional identification show that there are 6,605 different SCMHWs, of which the most prevalent types are DurationNormalAreaNormalMean‐intensityNormal, DurationNormalAreaNormalMean‐intensityExtreme, and DurationExtremeAreaExtremeMean‐intensityNormal. Additionally, SCMHWs mainly spread east‐west and move faster than they do north‐south. Over the long term, these events have become more frequent, longer in duration, broader in coverage, slower in movement, and have migrated greater distances.